Prozession, Ceylon - Stockhausen, Karlheinz 1928-2007 (Kürten Stockhausen Verlag, 1994)
PROZESSION / PROCESSION Version with tam-tam, electrochord, electronium,piano, filters, potentiometersCEYLON for electronium, camel bells with triangles and synthesizer, modulated piano,tam-tam, Kandy drum (Intuitive Music from the cycle FOR TIMES TO COME).